A FUZZY-BASED DECISION MAKING APPROACH FOR PRODUCT CONCEPT SELECTION - Ade Febransyah; J. Bely Utarja (Jurnal Teknik Industri: Jurnal Keilmuan dan Aplikasi Teknik Industri, 2004)
Selecting the best product concept is one of critical tasks in product development process. Making decisions at this stage becomes very difficult due to imprecise and uncertain product requirements. This paper presents the framework of product concept selection that integrates the fuzzy set theory and the analytic hierarchy process (AHP). In the proposed approach, the fuzzy membership function is employed in performing "pairwise comparison" between competing alternatives and a "reference" on each of the criteria. The use of a reference is due to the difficulty in consistently comparing concepts to one another. The comparisons are also used to obtain the relative importance of criteria with respect to the overall objective. Once pairwise comparisons are completed, vector aggregates are computed through the use of an original AHP method and fuzzy arithmetic operations. A numerical example is presented to illustrate the approach.